Comparison of chest compression quality between 2-minute switch and rescuer fatigue switch: A randomized controlled trial - Savatmongkorngul S. (2023)
Background: Rescuers performing chest compressions (CCs) should be rotated every 2 min or sooner if rescuers become fatigued. Is it preferable to switch rescuers when they become fatigued in such cases? This study was performed to compare the quality of CCs between two scenarios in hospitalized patients with cardiac arrest: 2-minute rescuer switch and rescuer fatigue switch. Methods: This randomized controlled trial involved 144 health-care providers, randomized to switch CC on the manikin model with 2-minute or rescuer fatigue. We recorded the CC quality for 20 min. Results: There were no significant differences in the percentage of target compressions, mean depth of compressions, or mean compression rate between the two groups. However, the rescuer fatigue switch group showed a significantly lower frequency of interruptions (4 vs. 9 times, P < 0.001) and a longer duration of each compression cycle (237 vs. 117 sec, P < 0.001). The change in the respiratory rate from before to after performing compressions was significantly greater in the 2-minute switch group (12 vs. 8 bpm, P = 0.036). Conclusion: The use of a rescuer fatigue switch CC approach resulted in no decrease in the quality of CC, suggesting that it may be used as an alternate strategy for managing in-hospital cardiac arrest.